The Influence Of Economic Literacy And Social Media On Employee Performance At Walenrang Health Centers In Luwu District - Bulan, Sari; Kusdarianto, Indra; Wahida, Altri (Jurnal Riset Akuntansi Terpadu, 2024)
Puskesmas is the health facility that is most easily accessible to the community because it is always available in every sub-district. In that case employees are able to work effectively and efficiently which results in their performance increasing. This study aims to determine how much influence economic literacy has on employee performance, social media on employee performance and economic literacy and social media together on employee performance at the Walenrang Health Center, Luwu Regency. The research method used is quantitative method with data collection techniques using questionnaire methods. The population at the Walenrang health center was 35 employees so that researchers used saturated samples due to the relatively small population. This research was processed with the SPSS22 (Statistical Package for the Social Science) application through multiple linear regression tests, partial tests, simultaneous tests and coefficient of determination tests.  Based on this research, it can be seen that at the Walenrang Community Health Center, through a partial test the economic literacy variable has a significant effect on employee performance while the social media variable does not have a significant effect, then in a simultaneous test the results were found that economic and social literacy together influence employee performance.